Resolução de problemas com adolescentes em conflito com a lei: uma proposta de intervenção - Padovani, Ricardo da Costa (2003)
Young offenders have always marked their presence in society, and constitute in a universal phenomenon. The goal of the present study involves the evaluation of an intervention program of young offenders based in the promotion of problem-solving skills aimed at improving their psycho-social well-being. The project s final goal involves the decrease of delinquent acts as a result of the intervention. The four male participants took part of NAI (Integrated Support Center), a temporary detention center for offenders in the city of São Carlos. Instruments used to assess psychological well-being were: Individual Interview, participants Weekly Self-reports, The Anger Disorder Scale, Beck Depression Inventory, Self-image Scale in addition to a Satisfaction with Treatment Questionnaire and monitoring of juvenile offenses. The intervention program consisted of 10 sessions, being 3 preintervention ones and 7 intervention sessions, which were daily and had one-hour duration. Besides problem-solving strategies, other techniques involved were: relaxation techniques, dysfunctional thoughts analysis, a functional analysis of impulsive/ aggressive behaviors, anger management, assertiveness training and time-out. Interviews provided rich data about the participants profile which were characterized as low-educational status, history of family violence and multiple offenses. Results indicated that two participants decreased their anger after the intervention; self-image was high since the study s beginning and all four presented a lower depression level. Follow-up data was obtained with only 2 participants, illustrating difficulties associated in working with this population.